GWAS in Africans identifies novel lipids loci and demonstrates heterogenous association within Africa. Issue 22 (1st July 2021) - Bentley, Amy R; Chen, Guanjie; Doumatey, Ayo P; Shriner, Daniel; Meeks, Karlijn A C; Gouveia, Mateus H; Ekoru, Kenneth; Zhou, Jie; Adeyemo, Adebowale; Rotimi, Charles N
Abstract: Serum lipids are biomarkers of cardiometabolic disease risk, and understanding genomic factors contributing to their distribution is of interest. Studies of lipids in Africans are rare, though it is expected that such studies could identify novel loci. We conducted a GWAS of 4317 Africans enrolled from Nigeria, Ghana and Kenya. We evaluated linear mixed models of high-density lipoprotein cholesterol (HDLC), low-density lipoprotein cholesterol (LDLC), total cholesterol (CHOL), triglycerides (TG) and TG/HDLC. Replication was attempted in 9542 African Americans (AA). In our main analysis, we identified 28 novel associations in Africans. Of the 18 of these that could be tested in AA, three associations replicated ( GPNMB -TG, ENPP1 -TG and SMARCA4 -LDLC). Five additional novel loci were discovered upon meta-analysis with AA (rs138282551-TG, PGBD5 -HDLC, CD80 -TG/HDLC, SLC44A1 -CHOL and TLL2 -CHOL). Analyses considering only those with predominantly West African ancestry (Nigeria, Ghana and AA) yielded new insights: ORC5 -LDLC and chr20:60973327-CHOL. Among our novel findings are some loci with known connections to lipids pathways. For instance, rs147706369 ( TLL2 ) alters a regulatory motif for sterol regulatory element-binding proteins, a family of transcription factors that control the expression of a range of enzymes involved in cholesterol, fatty acid and TG synthesis, and rs115749422 ( SMARCA4 ), an independent association near the known LDLR locus that is rare or absent in populations without African ancestry. These findings demonstrate the utility of conducting genomic analyses in Africans for discovering novel loci and provide some preliminary evidence for caution against treating 'African ancestry' as a monolithic category.